The Effect of Profitability, Liquidity, and Leverage on Dividend Policy of Manufacturing Companies Listed on the Indonesian Stock Exchange (BEI) LQ45 - Putri, Ni Gusti Ayu Putu Erli Diana; Suriani, Ni Nyoman; Dewi, Made Pratiwi (PT Keberlanjutan Strategis Indonesia, 2026)
Dividend policy is a reflection of managerial preferences in allocating profits between the interests of shareholders and long-term internal financing needs. In the context of manufacturing companies listed in the Indonesian LQ45 index, dividend distribution patterns exhibit inconsistent changes across periods, indicating complex policy dynamics. This study explores the role of profit performance, liquidity flexibility, and debt intensity on profit distribution decisions from 2019 to 2024. A quantitative approach was applied using secondary data from the financial statements of five manufacturing issuers consistently listed in the LQ45, analyzed through multiple linear regression. The study results indicate that profit-generating capacity is the dominant factor driving dividends, while liquidity tends to be neutral, and leverage actually limits the scope for profit distribution to shareholders.